Teacher’s Salary Differentials and the Quality of Educational Services : Recent Developments in Saskatchewan - Walmsley, P.; Ohtsu, M. (Relations industrielles / Industrial Relations, 1975)
This paper examines the relationship between teacher wage determination and the distribution of teacher skill-mix, based on recent Saskatchewan data. The authors argue that while centralized bargaining produces more uniform wage scale throughout the Province, it does not necessarily lead to the uniform distribution of teacher skill-mix among municipalities which is one of the most important conditions for the achievement of equality in the provision of educational services ; rather, it is the ability to pay of the individual school boards which has crucial bearings upon the composition of teacher skill-mix.